The process of illness in the light of a Cardiac Rehabilitation Program - Silviamar Camponogara, Marlusse Silveira, Letice Dalla Lana, Claudiane Bottoli, Karine Rossato, Camilla Barros (Revista de Enfermagem da UFPI, 2020)
DOI: https://doi.org/10.26694/reufpi.v3i3.1778